A re‐assessment of the infra‐generic classification of the genus Caulerpa (Caulerpaceae, Chlorophyta) inferred from a time‐calibrated molecular phylogeny. Issue 6 (9th October 2014) - Draisma, Stefano G.A.; van Reine, Willem F. Prud'homme; Sauvage, Thomas; Belton, Gareth S.; Gurgel, C. Frederico D.; Lim, Phaik‐Eem; Phang, Siew‐Moi; Verbruggen, H.
<x xml:space="preserve">Abstract</x> The siphonous green algal family Caulerpaceae includes the monotypic genus Caulerpella and the species‐rich genus Caulerpa. A molecular phylogeny was inferred from chloroplast tufA and rbcL DNA sequences analyzed together with a five marker dataset of non‐caulerpacean siphonous green algae. Six Caulerpaceae lineages were revealed, but relationships between them remained largely unresolved. A Caulerpella clade representing multiple cryptic species was nested within the genus Caulerpa. Therefore, that genus is subsumed and Caulerpa ambigua Okamura is reinstated. Caulerpa subgenus status is proposed for the six lineages substantiated by morphological characters, viz., three monotypic subgenera Cliftonii, Hedleyi, and Caulerpella, subgenus Araucarioideae exhibiting stolons covered with scale‐like appendages, subgenus Charoideae characterized by a verticillate branching mode, and subgenus Caulerpa for a clade regarded as the Caulerpa core clade. The latter subgenus is subdivided in two sections, i.e., Sedoideae for species with pyrenoids and a species‐rich section Caulerpa. A single section with the same name is proposed for each of the other five subgenera. In addition, species status is proposed for Caulerpa filicoides var. andamanensis (W.R. Taylor). All Caulerpa species without sequence data were examined (or data were taken from species descriptions) and classified in the new classification scheme. A temporal framework of Caulerpa diversification is provided by calibrating the phylogeny in geological time. The chronogram suggests that Caulerpa diversified into subgenera and sections after the Triassic‐Jurassic mass extinction and that infra‐section species radiation happened after the Cretaceous‐Tertiary mass extinction.